52.9k views
5 votes
What is the sum of (-2.1x+3.7) and (5+4.9x)?

User MHollis
by
4.8k points

2 Answers

5 votes
Hi there! The answer is 2.8x + 8.7

To find the sum of (-2.1x+3.7) and (5+4.9x), we must add both expressions.

(-2.1x+3.7) + (5+4.9x) =
First get rid of the parenthesis, which (now) don't have a function.

-2.1x + 3.7 + 5 + 4.9x =
Rearrange the expression

-2.1x + 4.9x
+ 3.7 + 5 =
Now I'll add all the variables 'x'.

2.8x + 3.7 + 5 =
Add once again, but now add the numbers.

2.8x + 8.7
~ Hope this helps you!

User Peregrine
by
5.5k points
2 votes
= (-2.1x + 3.7) + (5 + 4.9x)
combine like terms

= (-2.1x + 4.9x) + (3.7 + 5)
add in parentheses

= 2.8x + 8.7


ANSWER: 2.8x + 8.7

Hops this helps! :)
User BluePeppers
by
5.2k points